Leaving words to remember : Greek mourning and the advent of literacy - Derderian, Katharine, 1970- (Mnemosyne, Supplements, 2001)
This volume examines the influence of literacy on the development of different genres of mourning in ancient Greece. The oral tradition of lament in the Homeric poems forms the point of departure for close readings of epigraphic material and written texts commemorating the dead in the archaic and classical periods, including grave epigrams, threnoi, tragedy, and Athenian epitaphioi . These texts reveal the non-linear development of Greek literacy and offer insight into the ongoing influence of lament in diverse poetic genres and the evolving uses of death and mourning in different media. In particular, the discussion focuses on the role of writing in commemorating soldiers and the evolution of the written memorial into a historical and civic medium of communication.